YouTube Kids on Children’s English Communication Skills: Parents’ Beliefs and Attitudes - Friska, Yuliana (Universitas Pahlawan Tuanku Tambusai, 2025)
In recent years, there has been a significant increase in the consumption of internet-based video content by children. Digital platforms like YouTube Kids have emerged as a primary source of easily accessible information for children and are widely recognized for their significant contribution to early childhood education. This study aims to explore parents’ beliefs and attitudes towards YouTube Kids and its impact on children’s English communication skills. This study used semi-structured interviews and focus group discussions with 20 parents of children aged 3 to 7 years. The findings indicate that parents recognize the potential of YouTube Kids to enhance vocabulary acquisition and language skills. However, the parents emphasize the necessity of a balanced approach to screen time, advocating for the integration of traditional learning methods alongside digital media. The findings suggest that YouTube Kids can be a valuable resource for language development when used thoughtfully, underscoring the importance of parental involvement in maximizing its benefits. Future research should further explore the long-term effects of digital media on language development and the dynamics of parental engagement.